Concentrate supplementation for crossbred bulls to increase profitability of smallholder fattening operations in East Java, Indonesia - Ratnawati D; Cowley F; Mayberry D; Poppi D (Indonesian Center for Animal Research and Development (ICARD), 2015)
Growth rates of bulls in Indonesia raised in smallholder fattening systems are generally low due to inadequate nutrition. This study compared bull growth and farmer profit between two feeding management systems, namely traditional feeding (as control) and intervention feeding by supplementation with a high quality concentrate. Bos taurus-Ongole cross bred bulls (n=46) aged 1.5-2 years, owned by smallholder farmers, from two villages in East Java were used in this study. The bulls were divided into two treatment groups; control and intervention. Farmers in the intervention group were provided with a concentrate containing onggok, copra and palm kernel cake. Farmers were instructed to feed 4 kg DM of concentrate/bull/day in addition to their existing roughage diet for 161 days or until sold. No changes were made to the feeding or management of the bulls in the control group. Mostly control group farmers used local forages and agricultural by product as a feed, without any supplementation. The daily feed cost and the cost of 1 kg of liveweight gain was higher in the intervention group (IDR 8827 and IDR 11990, respectively) than that of the control group (IDR 2606 and IDR 5543, respectively). Moreover, the average daily gain of bulls in the intervention group (0.82 kg/bull/day) was higher than that of bulls in the control group (0.52 kg/bull/day), resulting in a greater profit for the fattening period. Daily income minus feed costs was higher for farmers in the intervention group (IDR 24182/day), compared to farmers in the control group (IDR 15774/day). It is concluded that although there were additional costs for feeding high-quality feeds, but higher growth rates of bulls resulted in greater profits for smallholder farmers.